A Descriptive Framework for Electronic Meeting Systems Based on the UML Language - Antunes, Pedro (2009)
A descriptive framework has the purpose to identify the major components of a system and their relationships. This paper proposes a descriptive framework for electronic meeting systems. Our intention is to clarify and organize the conceptually and functionally distinctive components that we find in this technology. The proposed framework simplifies the evaluation of EMS functionality by organizations. The adoption of the UML language increases the potential of communicating EMS requirements to IS developers. The paper presents the evaluation grids of a collection of 10 EMS highlighting what framework components are supported and what components have been ignored